THU0111 Frequency and predictors of sustained remission in patients with early rheumatoid arthritis treated with conventional synthetic disease modifying drugs. (12th June 2018) - Zanframundo, G.; Bugatti, S.; Manzo, A.; Benaglio, F.; Sakellariou, G.; Montecucco, C.; Caporali, R.
Abstract : Background: The management of patients with early rheumatoid arthritis (RA) should be aimed at reaching the target of disease remission as soon as possible. In order to prevent joint damage and disability, and eventually allow treatment withdrawal, the state of disease remission should be also maintained. Whilst point remission is frequently achieved in early RA, the sustainability of remission in clinical practice remains poorly investigated. Objectives: To investigate the prevalence and predictors of sustained remission in patients with early RA treated with conventional synthetic disease anti-rheumatic drugs (csDMARDs). Methods: We evaluated 533 RA patients from the Pavia early arthritis inception cohort not in remission at baseline with at least 24 months of follow-up. Patients had arthritis of short duration (<12 months of symptoms) and were treatment-naïve at presentation. After diagnosis, patients were initiated a treat-to-target regimen with methotrexate aiming at low disease activity according to the 28-joint disease activity score (DAS28 ≤3.2), and were seen at regular intervals (2 months in the first 6 months, then trimestrally). Point remission was defined as the achievement of DAS28 remission (<2.6) or SDAI (simplified disease activity index) remission (≤3.3) at any time point within the first 12 months. Sustained remission was defined as mean DAS28 <2.6 and mean SDAI≤3.3 in the 3 visits following first remission. The frequency and predictors of point remission and sustained remission were analysed by Cox and binary regression respectively. Results: 287/533 (53.9%) patients achieved point DAS28 remission and 234/533 (43.9%) point SDAI remission. Independent predictors of point DAS28 remission were male gender (HR [95% CI] 1.84 [1.36–2.50]), shorter symptoms' duration (HR [95% CI] 0.99 [0.98–0.99], a lower tender joint count at baseline (HR [95% CI] 0.97 [0.94–0.99]), better functional status (HR [95% CI] 0.74 [0.59–0.94]), absence of radiographic erosions (HR [95% CI] 1.52 [1.06–2.20]) and use of prednisone (HR [95% CI] 1.51 [1.36–1.74]). The same predictors were confirmed for point SDAI remission. Irrespective of the criterion, remission was maintained by only half of the patients at follow-up, resulting in sustained remission rates of 28% for DAS28% and 19% for SDAI in the entire cohort. At multivariate analysis, independent predictors of sustained remission according to either the DAS28 or the SDAI were lower time to achieve remission and deeper remission, whilst demographic factors, baseline disease activity and use of prednisone were not significant (figure 1). Using ROC curve analysis, the best discriminative ability for sustained remission were time to remission ≤4 months, DAS28 at remission ≤2.2 and SDAI at remission ≤1. Conclusions: Despite early diagnosis and prompt institution of goal-steered treatment strategies with csDMARDs, only a minority of RA patients experience sustained remission. Remission is more likely to be maintained if the target is attained rapidly after treatment institution and if joint and systemic inflammation are effectively suppressed. Disclosure of Interest: None declared